ダイ 27 ジ ナンキョク チイキ カンソク タイ エットウ タイ ホウコク 1986-1987 - 内藤, 靖彦; ナイトウ, ヤスヒコ; Naito, Yasuhiko (1988)
P(論文) 第27次南極地域観測隊越冬隊35名は1986年2月1日より昭和基地の運営を開始し, 1987年1月31日に終了した。この間昭和基地, みずほ基地を維持しつつ, 定常観測の他, 宙空系, 雪氷・地学系, 生物・医学系による研究観測を実施した。研究観測の中心は, 雪氷・地学系による「東クィーンモードランド雪氷研究計画」の実施であった。7年計画の最終年にあたり, 氷床流動測定を中心に内陸に旅行隊を出して諸観測を実施した。更に航空機によりアイスレーダー観測等も実施した。上記のほか, 昭和基地では宙空系によるマルチビームリオメーター観測, 短波レーダー観測, 雪氷・地学系による大気微量成分観測, 炭酸ガス濃度測定, 生物・医学系による「ヒト」の寒冷適応観測等を中心に実施した。沿岸域調査ではプリンスオラフ海岸, 宗谷海岸各露岩域における地衣類調査を重点に実施した。特にラングホブデ域には生物観測小屋を設置し, 長期に滞在しての野外調査を実施した。昭和基地においては, 基地の維持のための所定の設営活動のほかに, 基地の整備のための諸活動も数多く実施した。本報告は上記の諸活動の概要報告である。 The wintering party of the 27th Japanese Antarctic Research Expedition composed of 35 personnel carried out routine and research observations of more than fifty items at Syowa Station, Mizuho Station and Asuka Camp, along the coast of Lutzow-Holm Bay and the Prince Olav Coast for a period between February 1986 and January 1987. Among three major research programs such as monitoring study of the upper atmospheric phenomena at Syowa Station, glaciological study in the East Queen Maud Land area, medical and biological study at Syowa Station and in the coastal area of Lutzow-Holm Bay and Prince Olav Coast, special efforts were made on the glaciological survey. The traverse party was sent out from Syowa Station to Asuka Camp in order to conduct the JMR observation that enabled precise measurements of the ice sheet movement. Along the traverse routes, ice core drilling, ice radar observation, meteorite survey and others were also conducted. An airborn ice radar survey was also carried out in the East Queen Maud Land area. Among other observations at Syowa Station, multibeam riometer observation was carried out to measure cosmic noise absorption. Ozone, CO_2,and other minor constituents in the atmosphere were studied by a variety of methods. Along the coastal area of Lutzow-Holm Bay and Prince Olav Coast, 51 ice-free localities were visited to study biology of lichen. departmental bulletin paper